Membangun karakter guru Berbasis aksiologi - Mutmainah . (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
Building a teacher who has a characteristic personality if viewed from a philosophical aspect of axiology is to question the nature of the personality of the teacher because the teacher in carrying out his duties in educating children must be in accordance with the purpose of education where the teacher must be able to integrate all the character values into everyday life. In other words, these values are embedded in the teacher's personal, so that the teacher must fulfill the competencies of the educator and education staff in order to meet professional competence as a character educator who is finally able to instill these character values in students.